Analisis Perbandingan Sistem Logistik Jakarta dengan Papua - Bintang Arya Mahasyahputra; Putri Wulandari; Erika Dian Maharani; Arief Hardi Rahman; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia's logistics system still has weaknesses in various regions. Jakarta has a complete infrastructure but long dwelling time and congestion hamper distribution. Meanwhile, Papua is weak in various sectors, ranging from infrastructure, geography and topography, resulting in rising commodity prices due to expensive distribution costs. This research uses a literature study method with related scientific journal standards, logistical data, and several important supporting papers. The results state that Jakarta and Papua have a large inequality. Jakarta still has complete infrastructure, but road congestion and delays in handling goods slow down the process of goods distribution so that MPPT is still not too high. Meanwhile, Papua is limited to geographical infrastructure, and inadequate topography so that for some raw materials it becomes twice as expensive as a result of the high MPPT.